Phenotypic diversity characterization of Kalang and Thale Noi Buffalo (Bubalus bubalis) in Indonesia and Thailand: Perspectives for the buffalo breeding development - SUHARDI Suhardi; PIJUG SUMMPUNN; MONCHAI DUANGJINDA; SUWIT WUTHISUTHIMETHAVEE (Society for Indonesian Biodiversity, 2020)
Abstract. Suhardi, Summpunn P, Duangjinda M, Wuthisuthimethavee S. 2020. Phenotypic diversity characterization of Kalang and Thale Noi Buffalo (Bubalus bubalis) in Indonesia and Thailand: Perspectives for the buffalo breeding development. Biodiversitas 21: 5128-5137. Kalang (KBuf) and Thale Noi buffaloes (TBuf) are swamp buffalo breeds important for biodiversity resources and permeate culture, religion, meat supply, and livelihood in Indonesia and Thailand. This study aimed to analyze the phenotypic characterization within breeds of KBuf/TBuf using quantitative and qualitative performance to define diversity. A total of 240 buffaloes from North (NK), East (EK), South Kalimantan (SK), Indonesia, and Phatthalung (PT), Thailand were observed. Phenotypic characterization showed female TBuf had the highest quantitative variable values with significant difference (P<0.05) from KBuf. Also, SK KBuf males had the highest qualitative variable values with significant difference (P<0.05) from EK and NK. The morphometric indices showed male buffaloes from SK and PT had close index values (P>0.05) and females from EK, SK, and PT showed a close relationship (P>0.05). The cumulative index results demonstrated KBuf/TBuf as very good meat-producing livestock. In conclusion, variations in qualitative and quantitative variables indicate phenotypic diversity in KBuf/TBuf which is a basis to perform selection and breeding development through pedigree recording, reproductive efficiency, cross-breeding, and genetic modification to produce high-quality buffalo breeding stock. KBuf/TBuf can provide high-quality red meat through improved genetic quality, productivity, and economic management towards modern buffalo breeding development.